The immunogenicity of PRV ΔgE/TK/UL49.5 three-gene-deleted vaccine in mice - Chenmeng Ding; Yawei Sun; Xianfeng Zhang; Mengmeng Shi; Han Yang; Xin Zhou; Shuangshuang Li; Yongtao Li; Xia Yang; Linyang Yu; Lu Chen (Virology Journal)
Abstract Background Pseudorabies (PR) caused by the re-emerging of pseudorabies virus (PRV) variant has outbroken among PRV vaccine immunized swine in many pig farms, which has caused serious social and economic consequences since the end of 2011. The PRV UL49.5 protein can inactivate the transporter associated with antigen processing (TAP), thereby downregulating the cell surface expression of swine leukocyte antigen class I (SLA-I) to evade host immune surveillance. Methods In this study, based on the PRV ΔgE/TK strain, PRV ΔgE/TK/UL49.5 triple gene deletion strain was constructed through homologous recombination and deletion of the PRV UL49.5 gene by the Cre-LoxP system. Its growth curve and effect on SLA-I transcription level were determined. Preliminary studies were carried out on serum neutralizing antibody levels, IFN-γ and IL-4 cytokines levels in mice immunized with PRV ΔgE/TK/UL49.5, and the viral load and challenge protection in mice tissues after challenge. Results The growth characteristics of PRV ΔgE/TK/UL49.5 strain were similar to those of PRV ΔgE/TK strain. The level of SLA-I was returned to normal after the deletion of PRV UL49.5 gene. The immunization of PRV ΔgE/TK/UL49.5 did not affect the weight gain of mice. Immunized mice could induce high levels of serum neutralization antibodies and immune cytokines, including IFN-γ and IL-4, which could provide complete protection against virulent PRV challenge. No obvious pathological damage was observed in lung, brain and trigeminal ganglion of mice immunized with PRV ΔgE/TK/UL49.5, and the tissue viral load was the lowest. Conclusions PRV ΔgE/TK/UL49.5 strain can induce enhanced immunogenicity and had the potential to be used as a candidate strain.